Walking 200 min per day keeps the bariatric surgeon away - Pfaff, Daniel; Poschet, Gernot; Hell, Rüdiger; Szendrödi, Julia; Teleman, Aurelio A. (Heliyon, 2023)
Exercise and increased physical activity are vital components of the standard treatment guidelines for many chronic diseases such as diabetes, obesity and cardiovascular disease. Although strenuous exercise cannot be recommended to people with numerous chronic conditions, walking is something most people can perform. In comparison to high-intensity training, the metabolic consequences of low-intensity walking have been less well studied. We present here a feasibility study of a subject who performed an exercise intervention of low-intensity, non-fatiguing walking on a deskmill/treadmill for 200 min daily, approximately the average time a German spends watching television per day. This low-impact physical activity has the advantages that it can be done while performing other tasks such as reading or watching TV, and it can be recommended to obese patients or patients with heart disease. We find that this intervention led to substantial weight loss, comparable to that of bariatric surgery. To study the metabolic changes caused by this intervention, we performed an in-depth metabolomic profiling of the blood both directly after walking to assess the acute changes, as well as 1.5 days after physical activity to identify the long-term effects that persist. We find changes in acylcarnitine levels suggesting that walking activates fatty acid beta oxidation, and that this mitochondrial reprogramming is still visible 1.5 days post-walking. We also find that walking mildly increases gut permeability, leading to increased exposure of the blood to metabolites from the gut microbiome. Overall, these data provide a starting point for designing future intervention studies with larger cohorts.